2012
DOI: 10.1590/s1517-83822012000200045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activity of extracts of Tibouchina candolleana (melastomataceae), isolated compounds and semi-synthetic derivatives against endodontic bacteria

Abstract: This work describes the phytochemical study of the extracts from aerial parts of Tibouchina candolleana as well as the evaluation of the antimicrobial activity of extracts, isolated compounds, and semi-synthetic derivatives of ursolic acid against endodontic bacteria. HRGC analysis of the n-hexane extract of T. candolleana allowed identification of β-amyrin, α-amyrin, and β-sitosterol as major constituents. The triterpenes ursolic acid and oleanolic acid were isolated from the methylene chloride extract and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…It was also observed that the tested extract was inactive against E.coli, whereas the isolated compound exhibited a antimicrobial effect. However, in several previous experiments (Schinor et al 2007;Dos Santos et al 2012) also it has been found that the extracts do not inhibit the grow of microorganisms, but their isolated compounds demonstrate an antimicrobial effect. This is because components are present in the extract act antagonistically and thus reduce the activity of the extract.…”
Section: Discussionmentioning
confidence: 90%
“…It was also observed that the tested extract was inactive against E.coli, whereas the isolated compound exhibited a antimicrobial effect. However, in several previous experiments (Schinor et al 2007;Dos Santos et al 2012) also it has been found that the extracts do not inhibit the grow of microorganisms, but their isolated compounds demonstrate an antimicrobial effect. This is because components are present in the extract act antagonistically and thus reduce the activity of the extract.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, they possess antibacterial activity against aerobic and anaerobic pathogens of the oral cavity [2,9,11,12,25,31,32]. Therefore, this study aimed to verify the antibacterial activity of the oleoresin, fractions, subfractions, and the major compound dehydroabietic acid isolated from P. elliottii against bacteria that cause endodontic infections.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds extracted from various members of this genus show bioactive properties (Cruz and Kaplan, ). Antibacterial (Mosquera et al ., ; Scio et al ., ; dos Santos et al ., ), antifungal (Niño et al ., ; Kuster et al ., ), anti‐oxidant (Mosquera et al ., ; Scio et al ., ; Sirat et al ., ), anticancer (Jones et al ., ) and anti‐parasitic activit ies (Singha et al ., ; Mpalantinos et al ., ; Cunha et al ., ) have been reported.…”
Section: Introductionmentioning
confidence: 99%